LYME DISEASE. MODERN ISSUE CONDITION - M. Chemych; I. Lutai (Eastern Ukrainian Medical Journal, 2020)
Nowadays Lyme disease (systemic tick-borne borreliosis, Lyme borreliosis) remains one of the most widespread zoonotic diseases with inoculable transmission mechanism, with ixodic ticks as carriers and Borrelia burgdorferi sensu lato as causative agent. The disease is characterized by a staged course and severe damage to various organs and systems. In Ukraine, the natural foci of this disease are almost throughout the country. Sumy region occupies a leading place in terms of morbidity. In Ukraine, the most affected regions are: Kyiv (29.00 cases per 100 thousand population), Cherkasy (25.4), Vinnitsa (23.9), Sumy (25.89) regions and Kyiv city (22.54). Lyme disease is mainly registered in the spring-autumn period, this may be due to increased visits to recreation areas and seasonal activity of ticks (May–June, September–October). Scientific data about etiology, epidemiology, clinical course, diagnostics, therapy and disease preventive measures were analyzed. It was found that B. burgdorferi s. l. is one of the most widespread agents with inoculable transmission mechanism on the European continent, including Ukraine. There is no single worldwide conception concerning preventive measures, diagnostics and treatment, which necessitates further study of this problem. Detection of antibodies to B. Burgdorferi s. l. in the human blood serum is not an evidence of infection, but testifies previous contact with these pathogens and presence of high risk of Lyme disease development. To improve the epidemiologic situation concerning Lyme disease it is required to study sites of the disease in Ukraine more thoroughly, to improve epidemiological surveillance system by creating disease spread map for diseases which are transferred by ticks in Sumy region, to plan a series of anti-epidemic and preventive measures, which are of practical use for population, to prevent asymptomatic disease course and chronization.